2012
DOI: 10.2337/dc11-2044
|View full text |Cite
|
Sign up to set email alerts
|

Use of an Automated Bolus Calculator in MDI-Treated Type 1 Diabetes

Abstract: OBJECTIVETo investigate the effect of flexible intensive insulin therapy (FIIT) and an automated bolus calculator (ABC) in a Danish type 1 diabetes population treated with multiple daily injections. Furthermore, to test the feasibility of teaching FIIT in a 3-h structured course.RESEARCH DESIGN AND METHODSThe BolusCal Study was a 16-week randomized, controlled, open-label, three-arm parallel, clinical study of 51 adults with type 1 diabetes. Patients aged 18–65 years in poor metabolic control (HbA1c 8.0–10.5%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
167
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 107 publications
(178 citation statements)
references
References 20 publications
8
167
2
Order By: Relevance
“…43 In case of hyperglycemia or predicted hyperglycemia, the basal-bolus can suggest the patient to administer a correction bolus. The size of the correction bolus can be determined in the same way as the prandial bolus by solving the optimization problem (6).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…43 In case of hyperglycemia or predicted hyperglycemia, the basal-bolus can suggest the patient to administer a correction bolus. The size of the correction bolus can be determined in the same way as the prandial bolus by solving the optimization problem (6).…”
Section: Discussionmentioning
confidence: 99%
“…7 They decreased the risk of error in the determination of the insulin dosage, and are usually preferred by patients with T1D compared to manual bolus calculation. 6,[8][9][10] In the current bolus calculators, the bolus size is proportional to the CHO in the meals, and possibly corrected depending on the current glucose level and the estimated insulin on board. Typical bolus calculators are in the form is the estimated insulin on board.…”
Section: Special Sectionmentioning
confidence: 99%
See 1 more Smart Citation
“…22 A randomized controlled trial (RCT) of this technology showed no increase in hypoglycemia frequency despite HbA1c improvement of 0.7-0.8% in participants provided with a BG meter equipped with bolus calculation and simultaneous education on carbohydrate counting. 23 An observational study of the automated bolus calculator showed that fear of hypoglycemia was reduced along with an increased confidence in bolus calculation although actual hypoglycemia rate reduction was not available. 24 A systematic review of this technology shows a trend toward fewer hypoglycemic episodes per week, although failing to achieve statistical significance, and improved postprandial BG values.…”
Section: Better Insulin Deliverymentioning
confidence: 99%
“…48 Forty-three people with diabetes using MDI therapy were taught carbohydrate counting first and were then randomized into either using the Accu-Chek Aviva Expert bolus advisor or trained to mentally calculate insulin doses. Subjects had CGM testing at baseline and at the end of the study.…”
Section: Finer Detailsmentioning
confidence: 99%